I deserve to be Sad: The role of Entitlement on Depression among Students of Nasarawa State University Keffi, Nigeria - Larry, Uzoigwe Tobechi; Elvis, Uzoigwe Chinonso (Pancasila International Journal of Applied Social Science, 2024)
Correlational design was adopted to investigate the influence of psychological entitlement, spiritual entitlement and academic entitlement on depression among students of Nasarawa State University Keffi in Nasarawa state, Nigeria. Accidental sampling technique was used to select three hundred and sixteen students   Nassarawa state university Keffi.  Three standardized instruments were used to measure both the independent and dependent variables one hypothec was formulated and tested using multiple regression analysis and correlation. The findings of the study indicated that spiritual entitlement and its facets did not significantly predict depression academic entitlement did have the highest significant influence on students’ depressive state while psychological entitlement came next. The results of the study also show that both psychological entitlement and intellectual humility jointly and significantly predicted moral tolerance. It was concluded that subjective depression is associated with dispositional factors. The theoretical and practical implications of the findings were discussed.